COLOR, HEALTH, VEGETABLES - AN APPROACH: रंग, सेहत, सब्जियाँ - एक दृष्टिकोण - Srivastava, Pratibha (International Journal of Research -GRANTHAALAYAH, 2014)
Colors have great importance in our lives. Through them we get to know the conditions around us and know the effect of colors. Colors arise from the spectral activities when they meet the spectrum in the human eye. Originally, only seven colors of the rainbow are considered to be the father of colors. These seven colors are red, orange, yellow, green, sky, blue and purple. Human virtue religion has red, blue and green colors according to the virtual perception. Different types of objects, sources and categories etc. come from colors. The physical, properties of light sources such as light villian, inclusion, reflection, etc. are associated with which color combinations are known. रंगों का हमारे जीवन में बहुत महत्व है। इनके द्वारा हमें अपने चारों ओर की स्थितियों का ज्ञान होता है और रंगों का प्रभाव ज्ञात होता है। रंग मनुष्य की आँख में वर्णक्रम से मिलने पर छाया संबंधी गतिविधियों से उत्पन्न होते है। मूलरूप से इन्द्रधनुष के सात रंगों को ही रंगों का जनक माना जाता है। ये सात रंग लाल, नारंगी, पीला, हरा, आसमानी, नीला व बैंगनी है। मानवीय गुण धर्म में आभासी बोध के अनुसार लाल, नीला व हरा रंग होता है। रंगों से विभिन्न प्रकार से वस्तु प्रकाष स्त्रोत एवं श्रेणियां इत्यादि आती है। प्रकाष स्त्रोतोें के भौतिक, गुणधर्म जैसे प्रकाष विलियन, समावेषन, परावर्तन, इत्यादि जुड़े है, जिनसे रंग संयोजन ज्ञात होते है।